Preparation method of high-fatigue-resistance titanium alloy material for ultrasonic osteotome
By applying tensile stress during the aging treatment of TC4ELI titanium alloy material with ultrasonic bone knife, combined with non-isothermal cooling, refining and homogenizing grains, improving grain boundary characteristics, the problem of insufficient fatigue resistance of the material is solved, and the fatigue performance and service life are significantly improved.
Patent Information
- Application Number
- CN202510194023.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The existing TC4ELI titanium alloy materials are insufficient in the environment of repeated use, resulting in low service life and reliability of ultrasonic bone knives.
The method of non-isothermal cooling combined with aging stretching is adopted to apply tensile stress during the aging process, and the grain refinement and homogenization of the alloy is promoted through light stretching, improving the grain boundary characteristics, thereby improving the fatigue performance of TC4ELI titanium alloy.
It significantly improves the fatigue performance of TC4ELI titanium alloy, extends the service life of ultrasonic bone knife, and improves its fatigue life under high stress and high frequency fatigue loads.
Smart Images

Figure CN119843195A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical device materials, and particularly relates to a method for preparing a titanium alloy material for an ultrasonic bone cutter with high fatigue resistance. Background Art
[0002] Ultrasonic bone knives are widely used in orthopedic surgery for cutting and trimming bone tissue. They have become an important surgical tool due to their high efficiency and safety. TC4ELI titanium alloy, as an excellent biocompatible material, is widely used in medical devices due to its excellent corrosion resistance, strength and light weight. However, ultrasonic bone knives are often affected by complex mechanical loads (such as high-frequency vibration and repeated impact) during use, resulting in fatigue damage to the material. Therefore, improving the fatigue resistance of TC4ELI titanium alloy is of great significance to improving the service life and reliability of ultrasonic bone knives.
[0003] Although the current TC4ELI titanium alloy material can provide certain strength and corrosion resistance, it still has deficiencies in fatigue resistance, especially in the environment of repeated use, and there is a lack of effective regulation methods for the material's microstructure and fatigue behavior. Therefore, how to improve the fatigue resistance of TC4ELI titanium alloy by optimizing its microstructure has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a titanium alloy material for ultrasonic bone cutter with high fatigue resistance in view of the shortcomings of the above-mentioned prior art. The method adopts a non-isothermal cooling combined with aging stretching, and for the first time proposes to apply tensile stress during the aging process, promote alloy grain refinement and homogenization through light stretching, improve grain boundary characteristics, thereby significantly improving the fatigue performance of TC4ELI titanium alloy, and obtaining a titanium alloy material for ultrasonic bone cutter with high fatigue resistance.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a titanium alloy material for an ultrasonic bone cutter with high fatigue resistance, characterized in that the method comprises the following steps: Step 1: Heat the TC4ELI titanium alloy rod to 950°C~1050°C and keep it for 20min~40min to perform high temperature solution treatment to obtain a high temperature solution rod; Step 2: rapidly cooling the high temperature solid solution rod obtained in step 1 to 450°C~550°C at a cooling rate of 50°C / s~100°C / s, and performing non-isothermal cooling to obtain a non-isothermal cooled rod; Step 3: performing aging treatment on the non-isothermal cooled rod obtained in step 2 at a temperature of 450°C to 550°C for a time of 6h to 12h; Step 4: During the aging treatment in step 3, when the non-isothermal cooled rod is heated to the target temperature of the aging treatment, a tensile stress of 300 MPa to 700 MPa is applied to the non-isothermal cooled rod, and hot stretching is performed for 0.5 h to 2 h. After the hot stretching is completed, the tensile stress is unloaded and the aging treatment is continued to obtain an aged hot-stretched rod; Step 5: Cool the aged hot-stretched rod obtained in step 4 to room temperature and perform surface polishing to obtain a titanium alloy material for ultrasonic bone cutting with high fatigue resistance.
[0006] The present invention completely forms the β phase in the rod through high-temperature solution treatment. The precise control of temperature and time during the solution treatment is crucial, which helps to obtain a fine and uniform β phase structure, laying a foundation for subsequent grain transformation and fatigue performance improvement. The structural transformation of the alloy is achieved within a certain temperature range through non-isothermal cooling, and the precipitation of the second phase is controlled, so that the grains are refined and evenly distributed. In this process, rapid cooling can not only avoid the precipitation of coarse phases, but also provide a better foundation for subsequent aging treatment. Through aging treatment and hot stretching, and precise control of aging temperature and time, fine α phase particles are uniformly precipitated in the alloy to form a fine equiaxed crystal structure, and the grains are evenly distributed. The tensile stress and time are controlled to further refine the equiaxed crystals, and the organization is a fine and uniform α and β equiaxed crystal structure, and a certain number of small island-shaped β phases are distributed on the matrix of the evenly distributed equiaxed α phase. By performing surface polishing treatment, the surface oxide layer and impurities are removed to ensure a smooth and clean surface.
[0007] The above-mentioned method for preparing a titanium alloy material for ultrasonic bone cutting with high fatigue resistance is characterized in that the heating described in step one is performed by an induction coil, and the non-isothermal cooling described in step two is to monitor the temperature of the high-temperature solid solution rod in real time by a thermocouple, and adjust the power supply current to dynamically control the power of the induction coil to 0.5kW~3kW, and quickly cool to the target temperature. The present invention ensures the heating effect by using an induction coil for heating, and is convenient for adjusting the power to achieve non-isothermal cooling.
[0008] The above-mentioned method for preparing a titanium alloy material for ultrasonic bone cutting with high fatigue resistance is characterized in that the tensile stress in step 4 is controlled by a stretching machine clamped at both ends of the non-isothermal cooling rod. The present invention uses a stretching machine to stretch both ends of the non-isothermal cooling rod, thereby ensuring the uniformity of the stretching.
[0009] The above-mentioned method for preparing a titanium alloy material with high fatigue resistance for ultrasonic bone cutter is characterized in that the structure of the titanium alloy material with high fatigue resistance for ultrasonic bone cutter described in step five is a fine and uniform equiaxed crystal structure of α and β two-phases, and the β phase is distributed on the matrix of the uniformly distributed equiaxed α phase. The volume fraction of the equiaxed α phase in the structure is between 50% and 60%, and the equiaxed crystal size is 5μm to 15μm.
[0010] Compared with the prior art, the present invention has the following advantages: 1. The present invention adopts a method of non-isothermal cooling combined with aging stretching, and for the first time proposes to apply tensile stress during the aging process. By light stretching, the alloy grains are promoted to be refined and homogenized, and the grain boundary characteristics are improved, thereby significantly improving the fatigue performance of TC4ELI titanium alloy. The innovation of this process lies in utilizing the influence of tensile stress on the microstructure to regulate the grain morphology and grain boundary characteristics, which is a breakthrough in traditional heat treatment processes.
[0011] 2. The present invention optimizes the equiaxed crystal morphology and size distribution of TC4ELI titanium alloy by precisely controlling the parameters of solution treatment, non-isothermal cooling and aging treatment, especially ensuring uniform distribution of grains while controlling grain refinement. Small and uniform equiaxed crystals can significantly improve the fatigue life of the material, which has not been fully realized in existing heat treatment technologies.
[0012] 3. The present invention comprehensively regulates the microstructure of the alloy through a multi-stage heat treatment process, including solution treatment, non-isothermal cooling, aging treatment and hot stretching control, etc., which can significantly improve the fatigue life of TC4ELI titanium alloy, especially under high-frequency fatigue loads. Compared with the existing traditional heat treatment process, the present invention has significant advantages in improving fatigue performance.
[0013] 4. The present invention significantly improves the fatigue life of TC4ELI titanium alloy under high stress and high frequency fatigue loads by optimizing the equiaxed crystal morphology and size in the microstructure. Compared with untreated bars, the fatigue strength and fatigue life of the alloy are increased by 20% to 40%.
[0014] 5. The heat treatment process of the present invention is easy to promote and apply in industrial production and has strong adaptability. By adjusting the parameters during the heat treatment process, the alloy properties can be optimized according to different application requirements.
[0015] 6. The present invention provides a heat treatment process method for significantly improving the fatigue performance of TC4ELI titanium alloy by regulating the morphology, size and distribution of equiaxed crystals in the alloy. By optimizing multiple key parameters in the heat treatment process, precise control of the alloy microstructure is achieved to achieve the purpose of improving fatigue life.
[0016] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The present invention is a schematic diagram of the connection relationship between the induction coil, the non-isothermal cooling rod and the stretching machine clamp when hot stretching is performed during the aging treatment process.
[0018] Figure 2 This is the metallographic structure diagram of the TC4ELI titanium alloy rod used in Example 1 of the present invention.
[0019] Figure 3 This is the metallographic structure diagram of the titanium alloy material for high fatigue resistance ultrasonic bone cutter obtained in Example 1 of the present invention.
[0020] Figure 4 It is the admittance circle of the titanium alloy ultrasonic bone knife prepared in Example 1 of the present invention during ultrasonic vibration.
[0021] Figure 5 This is the admittance curve of the titanium alloy ultrasonic bone knife prepared in Example 1 of the present invention during ultrasonic vibration.
[0022] Figure 6 The schematic diagram is a structural diagram of a titanium alloy ultrasonic bone cutter made of the titanium alloy material for ultrasonic bone cutter with high fatigue resistance obtained in Example 1 of the present invention after ultrasonic vibration.
[0023] Figure 7 This is the metallographic structure diagram of the heat-treated titanium alloy obtained in Comparative Example 1 of the present invention.
[0024] Figure 8 This is the admittance circle of the titanium alloy ultrasonic bone knife prepared in Comparative Example 1 of the present invention during ultrasonic vibration.
[0025] Fig. 9 This is the admittance curve of the titanium alloy ultrasonic bone knife prepared in comparative example 1 of the present invention during ultrasonic vibration.
[0026] Fig.10 It is a schematic structural diagram of a titanium alloy ultrasonic bone knife prepared by using the heat-treated titanium alloy obtained in Comparative Example 1 of the present invention after ultrasonic vibration.
[0027] Description of reference numerals: 1—induction coil; 2—non-isothermal cooling rod; 3—stretching machine fixture. DETAILED DESCRIPTION
[0028] Figure 1 The schematic diagram of the structure of the induction coil, the non-isothermal cooling rod and the stretching machine fixture during the hot stretching in the aging treatment process of the present invention is shown in FIG. Figure 1 It can be seen that the induction coil 1 used for induction heating is sleeved on the outside of the non-isothermal cooling rod 2 to heat the non-isothermal cooling rod 2, and the stretching machine fixture 3 clamps both ends of the non-isothermal cooling rod 2, thereby realizing hot stretching during the aging treatment process.
[0029] Example 1 This embodiment includes the following steps: Step 1: Heat the TC4ELI titanium alloy rod to 960°C using an induction coil and maintain it for 30 minutes for high-temperature solution treatment to obtain a high-temperature solution rod; Step 2: The high-temperature solid solution rod obtained in step 1 is monitored in real time by a thermocouple, the power of the induction coil is dynamically controlled to be 3 kW by adjusting the power supply current, and the rod is rapidly cooled to 550°C at a cooling rate of 50°C / s to obtain a non-isothermal cooled rod; Step 3: Perform aging treatment on the non-isothermal cooled rod obtained in step 2 at a temperature of 550°C for 6 hours; Step 4: During the aging treatment in step 3, when the non-isothermal cooled rod is heated to the target temperature of the aging treatment, a tensile stress of 500 MPa is applied to the non-isothermal cooled rod by a stretching machine clamped at both ends of the non-isothermal cooled rod, and hot stretching is performed for 1.5 hours. After the hot stretching is completed, the tensile stress is unloaded and the aging treatment is continued to obtain an aged hot-stretched rod; Step 5, cooling the aged hot-stretched rod obtained in step 4 to room temperature and performing surface polishing to obtain a titanium alloy material for ultrasonic bone cutter with high fatigue resistance; Step 6: The high fatigue resistance ultrasonic bone cutter obtained in step 5 is machined with titanium alloy material to obtain a high fatigue resistance ultrasonic bone cutter.
[0030] Figure 2 The metallographic structure diagram of the TC4ELI titanium alloy bar used in this embodiment is shown in FIG. Figure 2 It can be seen that 80%-90% of the TC4ELI titanium alloy rod used in this embodiment is α phase, and the rest is small-sized β phase.
[0031] Figure 3 The metallographic structure diagram of the titanium alloy material for high fatigue resistance ultrasonic bone cutter obtained in this embodiment is shown in FIG. Figure 3 It can be seen that the microstructure of the high fatigue resistance titanium alloy material for ultrasonic bone knife obtained in this embodiment is a fine and uniform equiaxed crystal structure of α and β, a certain number of small island-shaped β phases are distributed on the matrix of the uniformly distributed equiaxed α phase, the volume fraction of the equiaxed α phase in the microstructure is greater than 50%, the equiaxed crystal size of the rod is 5μm~10μm, and the metallographic structure is uniform.
[0032] The titanium alloy ultrasonic bone cutter prepared in this embodiment was tested for the vibration frequency of the ultrasonic bone cutter by an ultrasonic vibrator and a transducer, and repeated 5 times, each test lasting 10 minutes, and fatigue performance, admittance circle and admittance curve were obtained to verify its performance. The results are shown in Figure 4 and Figure 5 , Figure 4 The horizontal axis is conductance G, and the vertical axis is susceptance B, which are used to analyze the admittance characteristics of the circuit, the curve admittance circle, and the trajectory of admittance changing with frequency in the polar coordinate system. Figure 5 In the figure, the red line is the logarithmic curve of impedance amplitude, the blue line is the impedance phase curve, the horizontal axis is the frequency Hz (logarithmic scale), and the vertical axis represents the logarithmic value of impedance amplitude (dB) when the curve is red, and the impedance phase angle (°) when the curve is blue. Figure 4 and Figure 5 It can be seen that the titanium alloy ultrasonic bone knife prepared in this embodiment is tested by an ultrasonic vibrator and a transducer. The vibration frequency is within the target range, the fatigue performance is good, no fracture occurs, and the admittance circle and the admittance curve are always normal.
[0033] Figure 6 FIG. 1 is a schematic diagram of the structure of a titanium alloy ultrasonic bone cutter made of titanium alloy material for ultrasonic bone cutter with high fatigue resistance obtained in this embodiment after ultrasonic vibration. Figure 6 It can be seen from the figure that the titanium alloy ultrasonic bone cutter made of titanium alloy material with high fatigue resistance obtained in this embodiment has a complete structure after ultrasonic vibration.
[0034] Comparative Example 1 This comparative example comprises the following steps: Step 1: Heat the TC4ELI titanium alloy rod to 960°C and keep it for 30 minutes to perform high temperature solution treatment to obtain a high temperature solution rod; Step 2, cooling the high temperature solid solution rod obtained in step 1 to room temperature with water; Step 3: Cool the high-temperature solid solution rod cooled to room temperature in step 2 to room temperature for aging treatment at a temperature of 550°C for 6 hours; Step 4, cooling the rod material after aging treatment in step 3 to room temperature and performing surface polishing treatment to obtain a titanium alloy material for ultrasonic bone cutting; Step 5: The ultrasonic bone knife obtained in step 4 is machined with titanium alloy material to obtain an ultrasonic bone knife.
[0035] Figure 7 The metallographic structure diagram of the heat-treated titanium alloy obtained in this comparative example is as follows: Figure 7 It can be seen that after this heat treatment in this comparative example, the structure of the titanium alloy is an α+β mixed dual-state structure, a part of the alloy structure is an equiaxed α phase and a lamellar α phase, and also includes a transformed β structure.
[0036] The titanium alloy ultrasonic bone knife prepared in this comparative example was tested for the vibration frequency of the ultrasonic bone knife by an ultrasonic vibrator and a transducer, and repeated twice, each test lasting 10 minutes, and fatigue performance, admittance circle and admittance curve were obtained to verify its performance. The results are shown in Figure 8 and Fig. 9 , Figure 8The horizontal axis is conductance G, and the vertical axis is susceptance B, which are used to analyze the admittance characteristics of the circuit, the curve admittance circle, and the trajectory of admittance changing with frequency in the polar coordinate system. Fig. 9 In the figure, the red line is the logarithmic curve of impedance amplitude, the blue line is the impedance phase curve, the horizontal axis is the frequency Hz (logarithmic scale), the vertical axis represents the logarithmic value of impedance amplitude (dB) when the curve is red, and represents the impedance phase angle (°) when the curve is blue. Figure 8 and Fig. 9 It can be seen from the figure that the admittance circle and the admittance curve are abnormal and broken after one vibration cutting.
[0037] Fig.10 The schematic diagram of the structure of the titanium alloy ultrasonic bone knife prepared by the heat-treated titanium alloy obtained in this comparative example after ultrasonic vibration is shown in FIG. Fig.10 It can be seen that the titanium alloy ultrasonic bone knife prepared from the heat-treated titanium alloy obtained in this comparative example breaks after ultrasonic vibration.
[0038] By comparing Example 1 and Comparative Example 1, it can be seen that in Comparative Example 1, no non-isothermal cooling was performed, and no aging treatment was performed under hot stretching conditions. Fracture occurred after two ultrasonic vibration tests. In Example 1, non-isothermal cooling was performed, and aging treatment was performed under hot stretching conditions. After five ultrasonic vibration tests, the structure was still intact, indicating that non-isothermal cooling and aging treatment under hot stretching conditions greatly improve the fatigue resistance of titanium alloy materials for ultrasonic bone cutters.
[0039] Example 2 This embodiment includes the following steps: Step 1: Heat the TC4ELI titanium alloy rod to 950°C using an induction coil and maintain the temperature for 40 minutes to perform high-temperature solution treatment to obtain a high-temperature solution rod; Step 2: The high-temperature solid solution rod obtained in step 1 is monitored in real time by a thermocouple, the power of the induction coil is dynamically controlled to be 2 kW by adjusting the power supply current, and the rod is rapidly cooled to 500° C. at a cooling rate of 70° C. / s to perform non-isothermal cooling to obtain a non-isothermal cooled rod; Step 3: performing aging treatment on the non-isothermal cooled rod obtained in step 2 at a temperature of 500° C. for 12 h; Step 4: During the aging treatment in step 3, when the non-isothermal cooled rod is heated to the target temperature of the aging treatment, a tensile stress of 300 MPa is applied to the non-isothermal cooled rod by a stretching machine clamped at both ends of the non-isothermal cooled rod, and hot stretching is performed for 2 hours. After the hot stretching is completed, the tensile stress is unloaded and the aging treatment is continued to obtain an aged hot-stretched rod; Step 5, cooling the aged hot-stretched rod obtained in step 4 to room temperature and performing surface polishing to obtain a titanium alloy material for ultrasonic bone cutter with high fatigue resistance; Step 6: The high fatigue resistance ultrasonic bone cutter obtained in step 5 is machined with titanium alloy material to obtain a high fatigue resistance ultrasonic bone cutter.
[0040] Example 3 This embodiment includes the following steps: Step 1: Heat the TC4ELI titanium alloy rod to 1050°C using an induction coil and keep it for 20 minutes to perform high-temperature solution treatment to obtain a high-temperature solution rod; Step 2: The high-temperature solid solution rod obtained in step 1 is monitored in real time by a thermocouple, the power of the induction coil is dynamically controlled to be 0.5 kW by adjusting the power supply current, and rapidly cooled to 450° C. at a cooling rate of 100° C. / s, and non-isothermal cooling is performed to obtain a non-isothermal cooled rod; Step 3: Perform aging treatment on the non-isothermal cooled rod obtained in step 2 at a temperature of 450° C. for 10 h; Step 4: During the aging treatment in step 3, when the non-isothermal cooled rod is heated to the target temperature of the aging treatment, a tensile stress of 700 MPa is applied to the non-isothermal cooled rod by a stretching machine clamped at both ends of the non-isothermal cooled rod, and hot stretching is performed for 0.5 h. After the hot stretching is completed, the tensile stress is unloaded and the aging treatment is continued to obtain an aged hot-stretched rod; Step 5, cooling the aged hot-stretched rod obtained in step 4 to room temperature and performing surface polishing to obtain a titanium alloy material for ultrasonic bone cutter with high fatigue resistance; Step 6: The high fatigue resistance ultrasonic bone cutter obtained in step 5 is machined with titanium alloy material to obtain a high fatigue resistance ultrasonic bone cutter.
[0041] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a titanium alloy material for an ultrasonic bone cutter with high fatigue resistance, characterized in that: The method comprises the following steps: Step 1: Heat the TC4ELI titanium alloy rod to 950°C~1050°C and keep it for 20min~40min to perform high temperature solution treatment to obtain a high temperature solution rod; Step 2: rapidly cooling the high temperature solid solution rod obtained in step 1 to 450°C~550°C at a cooling rate of 50°C / s~100°C / s, and performing non-isothermal cooling to obtain a non-isothermal cooled rod; Step 3: performing aging treatment on the non-isothermal cooled rod obtained in step 2 at a temperature of 450°C to 550°C for a time of 6h to 12h; Step 4: During the aging treatment in step 3, when the non-isothermal cooled rod is heated to the target temperature of the aging treatment, a tensile stress of 300 MPa to 700 MPa is applied to the non-isothermal cooled rod, and hot stretching is performed for 0.5 h to 2 h. After the hot stretching is completed, the tensile stress is unloaded and the aging treatment is continued to obtain an aged hot-stretched rod; Step 5: Cool the aged hot-stretched rod obtained in step 4 to room temperature and perform surface polishing to obtain a titanium alloy material for ultrasonic bone cutting with high fatigue resistance.
2. The method for preparing a titanium alloy material for an ultrasonic bone cutter with high fatigue resistance according to claim 1, characterized in that: The heating described in step one is performed by an induction coil, and the non-isothermal cooling described in step two is to monitor the temperature of the high-temperature solid solution rod in real time through a thermocouple, and adjust the power supply current to dynamically control the power of the induction coil to 0.5kW~3kW, and quickly cool it to the target temperature.
3. The method for preparing a titanium alloy material for an ultrasonic bone cutter with high fatigue resistance according to claim 1, characterized in that: The tensile stress in step 4 is controlled by a stretching machine clamped at both ends of the non-isothermal cooling rod.
4. The method for preparing a titanium alloy material for an ultrasonic bone cutter with high fatigue resistance according to claim 1, characterized in that: The microstructure of the titanium alloy material for the high fatigue resistance ultrasonic bone knife described in step 5 is a fine and uniform equiaxed crystal structure of α and β dual phases, with β phase distributed on a matrix of uniformly distributed equiaxed α phase, the volume fraction of the equiaxed α phase in the microstructure is between 50% and 60%, and the equiaxed crystal size is 5μm to 15μm.
Citation Information
Patent Citations
Heat treatment method of TC4ELI titanium alloy bar for ultrasonic scalpel and titanium alloy bar
CN115976439A
Preparation method for prolonging high-cycle fatigue life of TC4ELI alloy
CN116043151A
Method for improving ultrasonic fatigue performance of double-phase titanium alloy and double-phase titanium alloy ultrasonic knife
CN116397185A
Medical high-temperature-resistant high-strength ultrasonic osteotome titanium alloy and bar as well as preparation method and application thereof
CN118028657A
Thermal processing method for improving high-speed impact resistance of two-phase titanium alloy
US20250019813A1